Handbook of research on advanced techniques in diagnostic imaging and biomedical applications - Exarchos, Themis P. 1980-; Papadopoulos, Athanasios 1971-; Fotiadis, Dimitrios Ioannou; Gale Group (Hershey, Penn. Medical Information Science Reference, 2009)
Includes methodologies that introduce biomedical imaging in decision support systems and their applications in clinical practice. Provides readers with an overview of the emerging field of image-guided medical and biological decision support, bringing together various research studies and highlighting future trends.
Computational methods and tools for decision support in biomedicine: an overview of algorithmic challenges -- Integrating imaging and clinical data for decision support -- Analysis and quantification of motion within the cardiovascular system: implications for the mechanical strain of cardiovascular structures -- New developments in intracoronary ultrasound processing -- Diagnostic support systems and computational intelligence: differential diagnosis of hepatic lesions from computed tomography images -- Significance estimation in fMRI from random matrices -- Optimal diffusion encoding strategies for fiber mapping in diffusion MRI -- Segmentation of cardiac magnetic resonance images -- Image registration algorithms for applications in oncology -- Computer-aided diagnosis in breast imaging: trends and challenges -- Assessment of stroke by analysing carotid plaque morphology -- Quantitative analysis of hysteroscopy imaging in gynaecological cancer -- Combining geometry and image in biomedical systems: the RT TPS case -- Internal radionuclide dosimetry using quantitative 3-D nuclear medical imaging -- Diffusion tensor imaging and fiber tractography -- Image processing and machine learning techniques for facial expression recognition -- Developments and advances in biomedical functional infrared imaging -- DNA microarrays: analysis and interpretation -- Image processing and machine learning techniques for the segmentation of cDNA microarray images -- Recent advances in automated chromosome image analysis -- Machine learning in morphological segmentation -- Pit pattern classification using multichannel features and multiclassification -- Automatic identification and elastic properties of deformed objects using their microscopic images -- Nonlinear ultrasound radiation-force elastography -- Dynamic contrast enhancement: analysis's models and methodologies -- Automatic correspondence methods towards point-based medical image registration: an evaluation study -- Anomaly detection in medical image analysis -- Evaluation of medical image compression -- Advanced ROI coding techniques for medical imaging -- Segmentation methods in ultrasound images.
Electronic reproduction.
Keywords: Imaging systems in medicine -- Data processing -- Handbooks, manuals, etc; Diagnostic imaging -- Digital techniques -- Handbooks, manuals, etc; Electronic books